Take-Off Analysis of Wide-Body Aircraft in Various Conditions by Integral Performance Method - Sulistiya; Kusuma, Yudiawan Fajar; Satriya, Ilham Akbar Adi; Risnawan, Novan (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
The integral performance method is an alternative technique for estimating aircraft performance during take-off. This approach can be adaptable to various aircraft and take-off environmental conditions, and the calculations can be completed rapidly in a spreadsheet. This study takes the Boeing 747-400 aircraft, which has four engines, as an example to examine the impact of the aircraft and environmental factors on the necessary take-off distance for wide-bodied aircraft. Various All Engine Operative (AEO) and One Engine Inoperation (OEI) conditions are used to calculate the take-off distance. While OEI conditions include Continue Take-off (CTO) and Aborted Take-off (ATO), AEO conditions include normal conditions without rotation and normal conditions with rotation, the runway at an altitude of 3000 m, runway with a slope of 20 and 10 m/s headwind. The data used in this study include Boeing 747-400 aircraft characteristics such as wing configuration, engine performance, and environmental conditions. The analysis results show that altitude, runway slope, wind direction, and the percentage of thrusts used significantly affect take-off performance. Airport altitude contributes to aircraft performance, with higher altitudes requiring a longer take-off distance. The aircraft’s take-off distance on a runway with a 20 slope is greater than the normal take-off distance on a flat runway. Thrust reduced to 90% of maximum thrust results in a longer take-off distance than maximum thrust. A 10 m/s headwind will provide a longer take-off distance than ordinary circumstances without wind. The magnitudes of the Balanced Field Length (BFL) and V1 in the case of one engine inoperative (OEI) are 3200 meters and 85 meters per second, respectively.